Inequalities and crime - Vidali, Sofia (The Greek Review of Social Research, 2011)
The paper analyses the various aspects of inequality related to crime and social control in Greece. The author hypothesis is that inequalities relevant to social policy, constitute also preconditions of further inequalities in the various forms of criminality and of criminal justice system. The paper analyses issues related to the different forms of criminality, their impact in legal and illegal relations and their official representations by a critical criminological perspective. It is explored specifically the impact of social and economic inequalities within the criminal justice system operation regarding the respect for fundamental freedoms and rights. The paper concludes that a set of refusal and denials to recognise actual social problems concerning inequalities and discriminations related to the "social question", leads to the criminalisation of this last, and to the reproduction of inequalities and discriminations. The author asserts that these forms of inequality are also indicators of long-term cultivated occupational cultural attitudes and of de-humanisation of social relations processes and that they rather reveal a humanitarian crisis within the economic crisis in Greece.